Quality of sperm from cryopreserved semen of Tor soro in Dimethylsulfoxide and Glycerol 5, 10 and 15% - M. Zairin Junior; S. Handayani; I. Supriatna (Jurnal Akuakultur Indonesia)
Attempt to produce a lot number of Tor soro is difficult if only obtained by natural spawning since they often get mature in dissimilar time. Stock of sperm kept in enough number for fertilization in anytime is needed to overcome the problem.  Cryopreservation of semen is one of sperm cryopreservation methods using liquid nitrogen (-196oC) to quickly freeze the sperm. Several cryoprotectants can be utilized in cryopreservation.  In this study, quality by means of motility of cryopreserved sperm using dimethylsulfoxide or glycerol as cryoprotectant in the dose of 5, 10 and 15% were analyzed. The result of study show that percentage of sperm motile after cryopreservation using dimethylsulfoxide and glycerol was similar ranged from 76.7 to 83.3%.  Therefore, both cryoprotectant used in this study could be employed for cryopreservation of Tor soro sperm.